Male pre-christmas in the family health strategy: Reality or utopia (Research, Society and Development, 2021)
To evaluate the effectiveness of male prenatal care in the family health strategy. This is an exploratory - descriptive study, of a qualitative nature, with doctors and nurses from the Family Health Strategy, in the municipality of Cuité, state of Paraíba, with the collection of empirical material guided by a semi-structured script, strictly respecting the rules of Resolution 466 of 12/12/2012, submitted and approved by the Ethics and Research Committee of the Hospital Universitário Alcides Carneiro, under opinion No. 3,176,135. The data were formed using the Content Analysis technique. It was observed from the study that there is the implementation of the pregnant woman's prenatal care as recommended by the Ministry of Health, but the partner's prenatal care, even if recommended and recognized by the participants as relevant in the practice of the service, is still carried out in a timely manner and subsidized by other programs. With this study, it was possible to recognize the implantation and implementation of male prenatal care and the knowledge of USF professionals about it was identified. Nevertheless, it was found that the actions carried out with the parents are limited, requiring the woman to subsidize the adhesion of men to male prenatal care.